Effectiveness of the Pediatric Nursing Excellence Model on Nurses’ Knowledge and Practice in Pediatric Orthopedic Surgery Care: A Randomized Controlled Trial - Osama Mohamed Elsayed Ramadan; Alaa Hussain Hafiz; Nadia Bassuoni Elsharkawy; Nouran Essam Katooa; Areej Abunar; Enas Mahrous Abdelaziz; Samia Ibrahim Mabrouk Baraka; Mostafa Shaban; Nagwa Ibrahim Mabrouk Baraka (Children)
Background: Pediatric orthopedic nursing requires specialized competencies to optimize patient outcomes, particularly in the complex realm of pediatric surgery. This study explores the effectiveness of the Pediatric Nursing Excellence (PNE) Model in enhancing nurses’ knowledge and clinical practice in providing perioperative care for pediatric orthopedic patients in tertiary care inpatient settings. Methods: A double-blind, randomized controlled trial was conducted from February to July 2024, involving 100 nurses from two tertiary care hospitals in Tanta, Egypt. Participants were randomly assigned to receive PNE Model training (n = 50) or routine care (n = 50). Nurses’ knowledge, practical skills, and adherence to PNE principles were assessed at baseline, immediately post-intervention, and after one, three, and six months using validated tools. Results: The intervention group showed significantly greater improvements in knowledge (20.62 ± 6.7 vs. 8.16 ± 5.5, p < 0.001) and practice scores (62.28 ± 4.1 vs. 40.06 ± 14.7, p < 0.001) post-intervention, sustained over six months. Path analysis revealed that the PNE Model enhanced nursing practice directly (β = 0.25, p < 0.001) through improvements in engagement and adherence to excellence principles and indirectly (β = 0.53, p < 0.001) by significantly enhancing nurses’ knowledge (β = 0.70, p < 0.001), which in turn positively influenced their clinical practice (β = 0.75, p < 0.001). Post-intervention, 82% of nurses in the intervention group achieved high levels of professional excellence, compared to 8% at baseline (p < 0.001). Conclusions: The PNE Model demonstrates robust effectiveness in enhancing nurses’ knowledge, clinical practice, and professional excellence in pediatric orthopedic surgery care, with sustained long-term benefits. This evidence supports implementing specialized nursing education models to improve pediatric care quality in orthopedic settings.